SDR based radar demonstrator - Zou, Yingying. (2013)
Software defined radio (SDR) based radar is a new radar concept, which provides great flexibility in waveform diversity for various radar applications. Waveforms for SDR based radar is generated from computer adaptively in real-time based on the environment needs. Compared with conventional modern radar, simplicity and real time reaction are the great advantages. Its background information, concept and architecture are studied for a better understanding of this new radar concept.